2012
DOI: 10.1016/j.lfs.2012.08.002
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Reversion of hepatic steatosis by exercise training in obese mice: The role of sterol regulatory element-binding protein-1c

Abstract: Our study allows concluding that the reduction in SREBP-1c protein levels is associated with steatosis reversion induced by exercise training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 39 publications
0
18
0
2
Order By: Relevance
“…The silkworm pupae powder intake control group showed an increasing tendency. Considering the study results that after having obese rats exercise, the CPT-1 was increased by a significant degree [39] and that a high intensity intermittent exercise can also increase the CPT-1 [38], some of this study’s results can be explained. In addition, there emerged studies that reported a subsequent increase in the CPT-1 after feeding rats with an oil enriched in α-linoleic acid [31], and this can explain why the two groups that were fed with the silkworm pupae powder showed elevated levels of CPT-1.…”
Section: Discussionmentioning
confidence: 98%
“…The silkworm pupae powder intake control group showed an increasing tendency. Considering the study results that after having obese rats exercise, the CPT-1 was increased by a significant degree [39] and that a high intensity intermittent exercise can also increase the CPT-1 [38], some of this study’s results can be explained. In addition, there emerged studies that reported a subsequent increase in the CPT-1 after feeding rats with an oil enriched in α-linoleic acid [31], and this can explain why the two groups that were fed with the silkworm pupae powder showed elevated levels of CPT-1.…”
Section: Discussionmentioning
confidence: 98%
“…Besides enhancing free fatty acid oxidation in mitochondria, physical activity, particularly chronic aerobic exercise, may also reduce hepatic lipogenesis. In a high fat-fed mouse model, treadmill exercise substantially decreases the expression of sterol regulatory element-binding protein-1c (SREBP1c), a transcription factor triggering triglyceride synthesis (8). Chronic consumption of high fat or high carbohydrate diet elevates levels of inflammatory cytokines such as tumor necrosis factor alpha (TNFα) and interleukin-1β (IL-1β) (38).…”
Section: Beneficial Effects Of Exercise On Nafldmentioning
confidence: 99%
“…Exercise or physical activity has shown promising results in clinical studies as well as in experimental models of obesity and NAFLD management (5, 8). The beneficial effects of exercise on fatty livers have been recently attributed to widespread stimulation of autophagy during physical activity (18).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that physical exercise diminished the expression of genic transcription factors involved in lipid synthesis and increased lipolytic enzyme expression in eutrophic obese rats (Cintra et al, 2012) fed high-fat diets (42% Kcal) for two weeks (Yasari et al, 2010) and improved the mitochondrial functionality in genetically hyperphagic rats (accepted model of metabolic syndrome) (Rector et al, 2008b). Furthermore, in other studies, physical exercise improved the blood lipid profile, reduced body mass and visceral adiposity (Estadella et al, 2004), improved the glucagon action and (Charbonneau, Couturier, Gauthier, & Lavoie, 2005) insulin resistance condition (Marques, Motta, Torres, Aguila, & Mandarim-de-Lacerda, 2010).…”
Section: Discussionmentioning
confidence: 99%